ISOLASI DAN IDENTIFIKASI BAKTERI LIMBAH MINYAK BUMI DI STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DAN POTENSINYA SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI DI SMA - Hamdi Harmanzah; Irda Sayuti; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study was conducted to determine the isolation and identification of bacteria petroleum waste in public refueling stations (gas stations) and its potential as a learning module design in high school biology in March and April 2016. The results are used for designing learning modules on subjects biology. This research was conducted in two stages: stage of field research and design phase of learning modules. This research is descriptive and conducted by examination in the laboratory. The sampling technique in this study, done by using purposive sampling method. The results showed that the isolated bacteria found in soil or sand contaminated petroleum waste in the form of a spill or spills of gasoline at gas stations COCO 11,282,604 Pekanbaru and gas stations 14,284,623 Panam consists of three genera namely the genus Bacillus, Micrococcus and Pseudomonas, whereas isolates bacteria found in soil / sand contaminated with petroleum waste in the form of a spill or spills of diesel at gas stations COCO 11,282,604 Pekanbaru and gas stations 14,284,623 Panam consists of four genera namely the genus Bacillus, Citrobacter, Enterobacter, and Micrococcus. The results of this study can be used as a learning module design in high school biology in order to enrich the teaching materials on the concept of bacterial characteristics eubacteria.Keywords: Bacteria, Public Refueling Stations (Gas Stations), Learning Modules